KERAGAAN MODEL KEBIJAKAN PEMBANGUNAN EKONOMI SEKTOR IMMT DI SUMATERA UTARA - Eko Wahyu Nugrahadi (Quantitative Economics Journal, 2015)
Economic growth in North Sumatera (Sumut) in the last five years has increasedsignificantly. However, income inequality be widened. From the results of previous research has identified that one of the six sectors that have the most optimal possibilities for development as the development model of economic development of sectoral policies that can solve that problem in Sumut is the industry of food, beverages and tobacco (IMMT). The question needs further analysis to obtain a more in‐depth information in the development of that sector. Specifically, this study aims to identify the body of model of economic development policy in IMMT sector in addressing income inequality in the province of Sumut. The analysis is based on a model approach Social Accounting Matrix (SAM). For the purposes of analysis: (1) linkage, and (2) multiplier. Results of the analysis showed that IMMT have: (1) the index of sensitivityand power of dispersionis greater than one at a time, (2) forward and backward spread effect index larger than other sectors, (3) the second largest output multipliers, and (4) ranked sixth refers to the total sector.